Pemberdayan dan Peningkatan Kualitas Kesehatan Masyarakat di Dusun Jelapan - Fadhil, Adrian Yazid; Faatin, Salsa; Putra, Fedri Helio; Oktaviona, Fenta; Amiinuddin, Muhammad Wildan; Syauqiyah, Rifa; Aurellia, Tara Nur; Sinergi, Mu’afi; Wulandari, Kartika Ayu Putri; Muzakki, Java Arya; Indriawati, Ratna (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Public health issues, especially non-communicable diseases (NCDs), are the main focus of community service in Jelapan , Seloharjo Village, Pundong District, Bantul Regency. Based on data from the Pundong Community Health Center, around 30% of the population in Seloharjo Village suffers from hypertension and diabetes mellitus. The aim of this community service is to increase public awareness, knowledge, and skills in detecting and managing NCDs. The methods used include training in the use of medical devices (tensiometers and GCUs) for 15 health cadres and youth organization members, health counseling and screening for 40 residents, and family health care assistance for 6 families with members suffering from NCDs. The program was implemented through three main stages: initial observation to identify health problems in the community, program implementation which includes training, counseling, screening, and mentoring, and evaluation to measure the effectiveness of the program. The results of the service show a significant improvement in the knowledge and skills of the community. Before the training, all participants were able to use a blood pressure monitor, but only 3 (20%) were able to use a glucose meter. After the training, 100% of the participants were able to operate both devices properly. Basic knowledge about NCDs increased from 50% to 70% after the counseling. The family health care assistance program succeeded in increasing compliance in monitoring blood pressure, blood sugar levels, cholesterol, and uric acid, as well as encouraging the adoption of a healthy lifestyle such as diet regulation and physical activity. Cooperation with the Pundong Community Health Center and active community participation are important factors in the program's success. The program's sustainability can be seen from the ability of health workers to use medical devices independently and the increased community awareness of the importance of routine health checks. The success of this program is expected to be the first step in the ongoing prevention and control of NCDs in Jelapan.